The relations between body mass index, motor skills, and physical self-concept in determining physical activities of junior karatekas - Miroljub Ivanović; Uglješa Ivanović (Exercise and Quality of Life)
The aim of this research was to examine the contribution of body mass index (BMI), motor skills and physical self-concept in explaining the physical activity (PA) of adolescent karatekas (N=148). The average age of participants was 16,56 years (± 1,14). The following measuring instruments were used: Body Mass Index (BMI), Eurofit Physical Fitness Test Battery, Physical Self-Description Questionnaire (PSDQ), and Physical Activity Questionnaire for Adolescents (PAQ-A). The Cronbach's alpha coefficient was used to determine the internal consistency of the questionnaires. The results of the hierarchical analysis showed that the predictor variables explained 18,5% of the total variance of the criterion PA of junior karatekas. With their positive direction, the independent variables of the physical self-concept strength (β = 0.049; p < 0.01), flexibility (β = 0.037; p < 0.01) and self-respect (β = 0.019; p< 0.05) showed the maximum statistically significant contribution to predicting the variability of the participants' PA, which means that junior karatekas who manifest the higher level of perception on those variables exhibit the higher level of PA. This study confirmed that the applied instruments are valid and suitable to predict PA among adolescent athletes in Serbia.